2020
DOI: 10.30699/ijp.2020.119681.2306
|View full text |Cite
|
Sign up to set email alerts
|

Association of Human Papilloma Virus and Epstein-Barr Virus with Ovarian Cancer in Shiraz, Southwestern Iran

Abstract: Scan to discover online Background & Objective: Ovarian cancer is one of the most common cancers amongst women. The association of Human papillomavirus (HPV) and Epstein-Barr virus (EBV) with ovarian cancer is inconclusive; therefore, the aims of this study were to evaluate the frequency of HPV and EBV in malignant, borderline, benign and normal ovarian tissues. Methods: In this case-control study, 205 Paraffin-embedded ovarian tissue specimens including 68 malignant, 27 borderline, 65 benign, and 45 normal ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Epstein-Barr virus (EBV) is a double-stranded DNA virus [39]. In two different studies, the EBV positivity rate has been reported to be lower in the normal group than in OC patient groups [40,41]. It has moreover been reported that elevated EBV antibody titers may lead to increased risk of OC [42].…”
Section: Discussionmentioning
confidence: 99%
“…Epstein-Barr virus (EBV) is a double-stranded DNA virus [39]. In two different studies, the EBV positivity rate has been reported to be lower in the normal group than in OC patient groups [40,41]. It has moreover been reported that elevated EBV antibody titers may lead to increased risk of OC [42].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of FEPV involves simple local excision, and its recurrence is uncommon in patients (17,18). In pregnant women, surgery can be performed after pregnancy when vaginal vascularity has returned to normal (19).…”
Section: Discussionmentioning
confidence: 99%
“…Ten sections (10 µm) of the paraffin-embedded block were cut and undergo de-paraffinization as previously described (5). DNA was extracted using tissue DNA extraction Minikit (Yektatajhiz, Tehran, Iran) according to the manufacturer's instruction.…”
Section: Methodsmentioning
confidence: 99%
“…Viral infections including HPV, Epstein-Barr virus (EBV), hepatitis B and C viruses, human T-lymphotropic virus-1, and polyomaviruses are considered as the major risk factor for about 20% of all cancers (4)(5)(6). Thus, some studies proposed a possible link between viruses such as EBV, HPV, and cytomegalovirus (CMV) with esophageal carcinoma (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%